Observations on the early development of the kelpfish Myxodes viridis (Clinidae) with the first description of their spawning habitat in subtidal kelp forests (Lessonia trabeculata) (Revista de Biología Marina y Oceanografía, 2021)
The spawning sites, embryonic development, and initial larval stages were described for the Chilean kelpfish, Myxodes viridis. Six different egg clutches were found attached by an elastic filament to the fronds of the subtidal kelp, Lessonia trabeculata, at shallow depths (0-7 m). All egg clutches were cared by one large (>15 cm TL) male, and egg color varied depending on the developmental stage. Embryonic development until hatching was categorized into 7 stages, which were completed within about 18 days in the laboratory. Recently hatched larvae presented fully pigmented eyes, a well-developed mouth with major shape changes in the head during the first week suggesting their ability to feed on plankton early in their larval development.